(untitled) (Південний архів (історичні науки), 2023)
The purpose of the study is to analyse the international terminological base in different directions and approaches to defining definitions related to the tragic fate of European Jews during the Second World War. Since the modern scientific field contains diverse work on certain issues, the authors of this study focused their attention on the works that, in their opinion, are of some interest in outlining the definitions of the Holocaust, as professional scientific competence requires the observance of terminological unity as an indispensable component of it. Methods. In order to systematize the terminological apparatus of historical-scientific research, the study is performed in the context of a problem-thematic approach using general scientific methods of analysis and synthesis, which ensured the achievement of the purpose. Results. Terminology occupies a special place in the system of modern scientific knowledge, and the unambiguity of the terms indicates orderliness and accuracy. However, in practice, terms often acquire multiple meanings. One wordterm serves to express different concepts or events. In particular, the term genocide is used both in relation to the tragedy of European Jewry during the Second World War and in relation to the Holodomor in Ukraine. And, on the contrary, there are often two or more terms to denote the same concept, event, or phenomenon. An example of such usage is Holocaust, Catastrophe, Shoah, Hurban, when it refers to the mass extermination of the Jewish population by the Nazis during the Second World War, and not to other tragic events in the history of the Jewish people. Based on the unprecedented nature of the events, an apt term for the scientific use of the indicated problem, which would be understandable and with which the majority of scientists would agree, is substantiated. Conclusions. Currently, the term Holocaust is more familiar and understandable to most scholars, but there is still debate among researchers regarding its definitions. The term genocide was used in the first post-war years, which caused a lot of controversy. Leading specialists in the study of this problem proposed the terms Catastrophe, Shoah, Hurban; the last two from the late 1960s and early 1970s gave way to the Holocaust. In general, the term Holocaust, in our opinion, has a clear motivated definition, remains the most widely accepted and used in the world, and since the end of the 20th century and in Ukrainian historical science as well, which does not exclude the possibility of using the term Catastrophe.